THE SWAHILI CITY-STATES OF THE LAMU ARCHIPELAGO - 1585-1810 INTERNAL DYNAMICS, EXTERNAL DYNAMICS - (:unkn) unknown (My University, 2005)
The years 1585-1810 were a climax for the main Swahili city-state of the Lamu Archipelago, chiefly for Pate, which became a prominent centre of the East Africa coast. Through the study of the relationships between internal dynamics and external dynamics, this work surveys in a synoptic view their evolution at the edge of the African Continent and the Indian Ocean. From the end of the sixteenth century on wards Pate was the first settlement to benefit from the evolution brought by the sea. The city got linked to numerous networks and expanded. The Oromo migrations disrupted the mainland area but Pate succeeded in entering into profitable alliance with the newcomers. Around the mid-seventeenth century she came to dominate the region and freed herself from the Portuguese empire. Pate was then the main channel of the evolution which Swahili society experimented, before her decline at the end of the eighteenth century. The expansion of Pate was lead by some of its leading clans: the ‘waungwana’, who grew richer thanks to trade and gained power and prestige through their links with abroad. Nevertheless, because of the social permeability and the fluidity of the sources of legitimacy, their power was disputed. To secure their domination, the urban elites used and accentuated the social function of the moral qualities and symbols tied to urbanity and Islam. The borders of Swahili identity, highly ambiguous and porous, as were the social borders, were thus altered
Keywords: African Research